1981
DOI: 10.1063/1.329537
|View full text |Cite
|
Sign up to set email alerts
|

Structural model of sputtered fluorinated amorphous silicon

Abstract: Structure of a fluorinated amorphous-silicon alloy (a-Si:F), which is produced by the sputtering of Si in mixtures of Ar and SiF4 gases, is studied by transmission electron microscope (TEM). As a special technique to study the localization of both atomic species and particular types of Si-F configuration, the change of TEM micrograph due to anisotropic chemical etching of samples is observed, and it is compared with the similar changes in infrared absorption spectra and the Rutherford backscattering spectra. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…More recent studies [46] report the gradual orthopara conversion of the trapped D 2 in the deuterium analogue at 4.2 K and outline the effects of annealing and deposition rate on these properties [45]. In addition to the high-pressure H 2 found in hydrogenated amorphous silicon, molecular SiF 4 is also known to exist in the fluorine-doped derivatives [51][52][53][54]. For samples prepared by photochemical vapour deposition, Langford et al [54] have suggested that these SiF 4 molecules are contained within cages of much the same size as those containing the molecular H 2 in the hydrogenated material.…”
mentioning
confidence: 99%
“…More recent studies [46] report the gradual orthopara conversion of the trapped D 2 in the deuterium analogue at 4.2 K and outline the effects of annealing and deposition rate on these properties [45]. In addition to the high-pressure H 2 found in hydrogenated amorphous silicon, molecular SiF 4 is also known to exist in the fluorine-doped derivatives [51][52][53][54]. For samples prepared by photochemical vapour deposition, Langford et al [54] have suggested that these SiF 4 molecules are contained within cages of much the same size as those containing the molecular H 2 in the hydrogenated material.…”
mentioning
confidence: 99%
“…In particular, the presence of fluorine atoms suppresses the regrowth rate (5).Spear and LeComber (10) demonstrated in 1975 that the doping of a-Si is possible by the incorporation of hydrogen atoms. Since then intense research has been carried out on a-Si based alloys to study the resultant structures and properties, aiming at improving the material quality of a-Si for device applications (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Fluorinated amorphous silicon (a-Si:F) is a promising material for its stability against heating.…”
mentioning
confidence: 99%
“…For example, it is well known that voids are present in a-Si films prepared by the GD or the thermal evaporation method (17). It has also been shown that a-Si:F films prepared by sputtering of Si in mixtures of Ar and SiF4 gases consist of many small grains of a-Si network, with both Si-F4 bonds and Ar atoms localized at the grain boundaries (20). These undesired microstructures can seriously affect the material quality.…”
mentioning
confidence: 99%